Educator Equity Policy in The Era of Decentralization: A Triple Helix Approach Model - Septi Wulandari; Suprapti Suprapti; Esa Septian (Universitas Sebelas Maret, 2024)
Tripe Helix's Approach to Equitable Educator Quality Policy in the Era of Decentralization. One of the findings in the obstacles to the implementation of educational decentralization is the equal distribution of teaching staff equality. The efforts made by the central government to improve the standard of national education are carried out against the backdrop that it is on its way to achieving the goal of creating superior human resources. It is difficult to find human resources who are both academically capable and emotionally robust. In the decentralized age, this article seeks to offer a